Commodities and development report 2017 commodity markets, economic growth and development (United Nations, 2017)
"The 2017 Commodities and Development Report investigates the transmission channels through which commodity dependence affects micro- and macro-level development outcomes, examines long-term commodity price trends and simulates their impacts on economic agents, and highlights challenges and lessons from ten commodity-dependent developing country case studies. The report concludes that country-level strategies aimed at the achievement of the Sustainable Development Goals (SDGs) must address commodity dependence in order to be successful."--Provided by publisher.